Learning Agility and Inclusive Leadership on Innovative Work Behavior: The Mediating Role of Work Engagement and Job Autonomy in Platform-Based Companies - Nabila Mufida Li Dinillah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Platform-based companies in Indonesia face significant challenges due to globalization, technological advancements, and the VUCA era, making innovation crucial for sustaining growth and organizational sustainability. This study aims to examine the impact of Learning Agility and Inclusive Leadership on Innovative Work Behavior (IWB), with the mediating roles of Work Engagement and Job Autonomy. The research employs a quantitative confirmatory approach with a cross-sectional design. Data was collected through a 44-item questionnaire from a sample of 255 employees of platform-based companies, selected using purposive sampling. Data analysis was conducted using Covariance-Based Structural Equation Modeling (CB-SEM) with LISREL 8.8. The results indicate that Learning Agility, Work Engagement, and Job Autonomy have a direct effect on IWB, while Inclusive Leadership does not directly influence IWB. Work Engagement and Job Autonomy play a significant mediating role. These findings provide practical insights for platform-based companies to consider Learning Agility and Inclusive Leadership in enhancing Work Engagement and Job Autonomy, ultimately fostering Innovative Work Behavior.